Społeczność żydowska w Łodzi w latach 1945-1950. Zarys problemu - Olejnik, Leszek (Acta Universitatis Lodziensis. Folia Historica, 1997)
Between 1945 and 1950 Łódź was the biggest city centre of Jews who had survived the Holocaust. In the second half of 1946 (alter the repatriation from USSR) about 20-30,000 Jews lived there (according various sources). Their population decreased later. About 10-15,000 Jews stayed there after a surge of the emigration to Israel (1949-1950) and their national separateness was emphasized more and more weakly. A main organization of this environment was Wojewódzki Komitet Żydowski (The Provincial Jewish Board), established in Februar 1945, which was under the authority of Centralny Komitet Żydów w Polsce (The Central Jewish Boaid of Poland). The Board was engaged in protective and cultural activity first of all. It organized kindergartens, day-rooms, pupils’ hostels and orphanages. The action for productiveness of Jews was also an important form of its activity. There were 11 Jewish political parties then and also many sociétés and other organizations, including Jewish national funds, supporting the fight for Jewish state m Palestine. The Jewish Religious Congregation was also active. Since 1945 Łódź was the main centre of Jewish cultural life. Headquarters of the most important Jewish organizations were established in Łódź as well as well-known cultural creators and activists settled there. The first after-var Jewish paper „Dos Naje Lebn” was published there (among more than 20 others). The Jewish Theatre was revived and existed actively under an artistic management of Ida Kamińska. Musicians, artists, cinema people had also great achievments. 2 Jewish schools existed. Since the end of 1940s these rich and various forms of activity of Jewish community were gradually limited.